Digital Media Use and its Implication for Sleep Disruption in Patients with ASD: A Qualitative Review with a Focus on The COVID19 Pandemic - Um*, Yuna; Iskenderian*, Nicholas; Liu, MD, PhD, Jun (North American Journal of Medicine and Science, 2021)
Autism spectrum disorder is a complex neuropsychiatric disorder characterized by impaired social communication and repetitive and restricted behavioral patterns. Patients often have multiple systemic comorbidities, such as a high prevalence of sleep disturbance. Sleep is regulated by the highly complex interplay between environmental cues, internal hormonal state, as well as neuronal circuitry. In particular, exposure to blue light from electronic devices directly impacts sleep regulation. In patients with ASD, electronic devices are double-edged swords: while they may increase blue light exposure, they often have therapeutic roles that are unique to this patient population. Sleep disorders have detrimental emotional and physical consequences, such as exacerbating behavioral dysregulation and difficulty in social communication in patients with autism. During the COVID19 pandemic, screen time exposure for people of all ages and backgrounds, including patients with autism, increased dramatically. In this qualitative review, we first summarize the recent literature on the mechanisms of sleep regulation and the importance of adequate sleep in patients with ASD. Second, we discuss the pros and cons of electronic device use in patients with ASD. Next, we assess the extent of screen time exposure in patients with autism prior to and during the COVID19 pandemic, in comparison to the control cohorts. We evaluate evidence for altered sleep duration/quality, and behavioral consequences of sleep disturbances based on the recent literature, especially those emerging from the pandemic. Finally, we make recommendations, based on our clinical experience and literature evidence, regarding measures to limit screen time to only productive use for patients with autism. [N A J Med Sci. 2021;1(1):012-020. DOI: 10.7156/najms.2021.1401012] Key Words: Autism spectrum disorder, sleep disruption, anterior hypothalamus, central nervous system, blue light, electronic devices